Geographical education: problems of construction textbook of geography for middle school (Journal of Geography and Environmental Management, 2018)
Currently, the main factors determining the development of geographic education are humanization, ecologization, politicization, globalization and informatization of the content of education. Among theareas of geographical science, research on the problems of nature management and geoecology, the sustainable development of society and nature, problems of socio-demographic and political-geographicalcharacter are topical. In this connection, the purpose of the geography textbook in the educational process is that it should be a “strategic model” of the learning process, as it reflects the aims of education,the content of education, teaching methods and organizational forms. Simultaneously, the textbook is a “tactical model” of the learning process, as it reveals the sequence of presentation of the teaching material and sets the scenario for the learning process. The aim of the study is to substantiate the content of the geography textbook for secondary schools as an integrated information and activity model of the educational process that reflects the goals, principles, content and technology of the learning process. A textbook is a model in the sense that it not only reflects the structure and content of a certain didactic-methodical system, but also projects its implementation. The scientific and practical significance of the research is that the didactic principles of the construction of a school textbook are proposed, the informational core of which is its multifunctionality; a structural-content model of the school textbook was defined; developed science-based requirements for building a school textbook of geography and practical recommendations for future authors of textbooks. The methodological basis of the research was the current provisions on the personality-activity approach in teaching, the theory of the textbook and the theory of a holistic pedagogical process, the concepts and standards of school geographic education. In this connection, the structure and content of the geography textbook, oriented to the student’spersonal development activity, should assume the appropriate types of educational activity. In the textbook, the goals and objectives of education, the ways to organize the learning situations, the necessaryinformation for the formation of knowledge and competencies, the ways of solving problems, the types of generalization and systematization, consolidation and control, the organization of independent works,the reflection of educational activity and the expected results are proposed. The activity function of the textbook implements the creative educational activity of students and their evaluation position in relation to the material being studied. This approach guarantees the learner increased motivation and effectiveness of training.